The Effect of Job Satisfaction and Organizational Commitment on Organizational Citizenship Behavior at PT. Swadharma Sarana Informatika Operational Head Office - Alghifari, Abizar; Yaman, Bahrul (Laboratorium Riset Ekonomi, 2024)
This research aims to analyze the influence of job satisfaction and organizational commitment on organizational citizenship behavior (OCB). This research uses a quantitative approach with research subjects at PT Swadharma Sarana Informatika Operational Head Office. Determining the sample in this research used a non-probability sampling method with a convenience sampling technique using the Slovin formula to determine the number of respondents, so that only 75 employees were used as the sample for this research. Data were collected using a questionnaire which was then analyzed using multiple linear regression with the help of SPSS version 25 software. The research results showed that Job Satisfaction and Organizational Commitment had a simultaneous effect on Organizational Citizenship Behavior (OCB). Partially, Job Satisfaction influences Organizational Citizenship Behavior (OCB), Organizational Commitment influences Organizational Citizenship Behavior (OCB). And the Adjusted R2 value is 0.645 or 64.5%.